12th International Symposium on High-Temperature Metallurgical Processing - Peng, Zhiwei; Hwang, Jiann-Yang; White, Jesse F.; Downey, Jerome P.; Gregurek, Dean; Zhao, Baojun; Yücel, Onuralp; Keskinkilic, Ender; Jiang, Tao (Metallurgist); Mahmoud, Morsi M. (Minerals, metals & materials series., 2022)
This collection includes the analysis, development, and operation of high-temperature processes that involve the extraction and processing of material resources, production, and treatment of metals, alloys, and ceramic materials. Contributions describe innovative methods for achieving property enhancement, impurity segregation and removal, byproduct recovery, waste minimization, energy efficiency, and utilization of complex ores. Also included are various technical, economic, and environmental issues associated with commercial-scale high-temperature processing methods.